Maxillomandibular Transverse Osteodistraction: A Multidisciplinary Case Report with 30-Month Follow-Up. (1st February 2020) - Turatti, G.; Bruni, A.; Savoini, M.; Giordano, M.; Gerbino, G.
Abstract : Aim . To describe a multidisciplinary treatment to correct a severe II class malocclusion with reduced both maxillary and mandibular transverse dimensions and dental crowding. Case Report . A 17-year-old young woman presented with an increased overjet complaining chiefly of forwardly placed upper front teeth and unpleasant smile aesthetics. The patient facially exhibited a gently convex profile, severe mentalis strain on lip closure, and dark buccal corridors. The intraoral assessment indicates Class II molar relationship bilaterally, mandibular and maxillary anterior crowding, and narrow shape of upper and lower arches. The cephalometric evaluation of the lateral radiograph of the skull evidences a skeletal Class II with a reduction of lower face height. Based upon the diagnostic records and consultation with the patient, surgically assisted expansion of both arches using bone-borne distractors, comprehensive orthodontic treatment, and combined jaw surgery was planned. Results . This approach permitted achieving most of the desired objectives in approximately 30 months. The follow-up records 30 months after treatment conclusion showed a stable occlusion. No complications were clinically and radiographically noticeable during the follow-up.